The impact of visualisation on the quality of chemistry knowledge - Vrtačnik, Margareta (Informatica (Ljubljana), 2000)
The most importanr result of the long-term project entitled Computer literacy is that the majority of Slovenian primary and secondary schools are now equiped with multimedia computers and with LCD projectors. However, these computerised classroms should not be used only for teaching computer science and informatics; they should also serve for teaching and learning other subjects e.g. chemistry, physics, languages, etc. Internet offers chemistry teachers previously unavailable possibilities for bridging the gap between concrete and abstract chemical concepts and processes. research on the spatialability of students and the quality of knowledge show that well developed spatial abilities enable better results whwn solving complex chemical problems, espacialy when dealing with 2-D representation of 3-D chemical structures. In this article we discuss how chemistry teachers can usespecialized Internet websites for visualising chemical structures and processes on the macro- and microscopic level, and correlate properties of molecules with their structure. We also present results which demonstrate the effects of different visualisation elements on the quality of chemical knowledge.
Keywords: multimedija; chemistry; kemija; poučevanje